Pre-service teachers’ pedagogical knowledge and attitudes towards slow learner students - Sintawati, Mukti; Sukma, Hanum Hanifa; Mardati, Asih; Feruzi, Sadiki Moshi; Satrianawati, Satrianawati (Journal of Education and Learning (EduLearn), 2024)
The pedagogical knowledge and acceptance of pre-service teachers towards slow learner students contribute to the implementation of inclusive education in regular schools. This study investigates the level of knowledge and acceptance pre-service teachers have in applying effective teaching strategies for students with slower learning needs. The participants of this study were 187 students at a private university in. This research is ex-post facto research. The research instrument used was a pedagogical knowledge test and attitude questionnaire. The data obtained were analyzed using correlation analysis, and t-test, to determine the relationship between pedagogical knowledge and attitudes towards slow learner students. The finding reveals that there was a positive relationship between pedagogical knowledge and attitudes towards slow learners, but the correlation between the two is not strong, in the medium category. Pre-service teachers gain pedagogical knowledge from inclusive education courses. Pre-service teachers also form a positive attitude towards slow learner students because of their experience interacting with slow learner students. A strong correlation between the variables in this study suggests that pre-service teachers' pedagogical knowledge has a limited impact on their attitudes toward slow learners. This highlights the need for improved training in effective teaching strategies for slow learners.